About formation of early forms of culture (Journal of Philosophy Culture and Political Science, 2019)
The article discusses various aspects and in sequence data on the evolution of the physical type of direct human ancestors accumulated by modern science. Theoretically it is based on the fact that a change in physical type of the earliest people exerted a great infl uence on the early development of culture. The author draws conclusions about the genesis of the earliest forms of human culture and its dependence on anthropogenesis, the process of becoming man himself. In light of the labor theory of anthropogenesis work activity was the main point of directing the evolution of the oldest and ancient people. Existing knowledge of Paleolithic culture allow us to speak about three stages of its development - the lower, middle and upper Paleolithic. The main idea of this paper is the author's idea that the natural morphological criteria of the hominid family are the symptoms referred to as the triad of hominid. Keywords: ancient culture, anthropogenesis, anatomic structure, type of direct ancestors, anthropological signs, creative activity.